Novel Laser System-Assisted CT-Guided Percutaneous Transthoracic Lung Biopsy in Patients with COPD Combined with Pulmonary Nodules - Li C; Hu X; Li C; Jiang G; Jiang YL (International Journal of COPD)
Chao Li,1,2 Xiao Hu,1 Cheng Li,1 Gang Jiang,1 Yong Liang Jiang1,2 1Department of Respiratory Medicine, Hunan Provincial People’s Hospital (The First-Affiliated Hospital of Hunan Normal University), Changsha, Hunan Province, People’s Republic of China; 2Clinical Medicine Research Center for Respiratory Rehabilitation in Hunan Province, Changsha, Hunan Province, People’s Republic of ChinaCorrespondence: Yong Liang Jiang, Department of Respiratory Medicine, Hunan Provincial People’s Hospital (The First-Affiliated Hospital of Hunan Normal University), No. 61 Jiefang Xi Road, Changsha, Hunan, People’s Republic of China, Tel/Fax +86-0731-83929527, Email yvfei316@163.comObjective: The diagnosis and management of pulmonary nodules in patients with COPD are challenging, as these nodules may represent either lung cancer or other pulmonary diseases. This study aims to evaluate the efficiency of a novel laser systems (LGS)-assisted CT-guided percutaneous lung biopsy in COPD patients with pulmonary nodules.Methods: A retrospective analysis was conducted on the data of 60 COPD patients with pulmonary nodules. Thirty patients (n=30) underwent CT-guided percutaneous transthoracic lung biopsy assisted by LGS, while the remaining 30 (n=30) underwent conventional manual CT-guided percutaneous transthoracic lung biopsy. The surgical time, number of punctures, CT scan frequency, and complications were compared between the two groups.Results: No significant differences were found between the two groups in terms of clinical characteristics, lesion size, location, puncture depth, or nodule nature. Compared to the traditional method, LGS-assisted CT-guided percutaneous lung biopsy significantly reduced the number of CT scans (2.3 ± 0.5 vs 3.2 ± 0.6, P < 0.001) and the average procedure time (12.6 ± 2.7 min vs 25.1 ± 3.4 min, P < 0.001). Additionally, the total intraoperative time per procedure was significantly reduced (25.1 ± 3.4 min vs 45.9 ± 8.8 min, P < 0.001). With the use of LGS, 73% (22/30) of the procedures hit the target on the first needle insertion, compared to only 6.7% (2/30) in the conventional group. Furthermore, there was no significant difference in the incidence of complications between the two groups.Conclusion: Compared to the traditional method, the use of LGS improved puncture efficiency in COPD patients, reduced the need for needle adjustments, and effectively shortened the procedure time.Keywords: novel laser systems, pulmonary nodules, COPD, PTNB, CT